Organic photovoltaic greenhouses: a unique application for semi-transparent PV? - Emmott,CJM; Roehr,JA; Campoy-Quiles,M; Kirchartz,T; Urbina,A; Ekins-Daukes,NJ; Nelson,J (Energy & Environmental Science, 2015)
Organic photovoltaics are an emerging solar power technology which embody properties such astransparency, flexibility, and rapid, roll to roll manufacture, opening the potential for unique nicheapplications. We report a detailed techno-economic analysis of one such application, namely thephotovoltaic greenhouse, and discuss whether the unique properties of the technology can provideadvantages over conventional photovoltaics. The potential for spectral selectivity through the choice ofOPV materials is evaluated for the case of a photovoltaic greenhouse. The action spectrum of typicalgreenhouse crops is used to determine the impact on crop growth of blocking different spectral rangesfrom the crops. Transfer matrix optical modelling is used to assess the efficiency and spectrally resolvedtransparency of a variety of commercially available semi-conducting polymer materials, in addition to anon-commercial low-band-gap material with absorption outside that required for crop growth. Economicanalysis suggests there could be a huge potential for OPV greenhouses if aggressive cost targets can bemet. Technical analysis shows that semi-transparent OPV devices may struggle to perform better thanopaque crystalline silicon with partial coverage, however, OPV devices using the low-band-gap materialPMDPP3T, as well as a high efficiency mid-band-gap polymer PCDTBT, can demonstrate improvedperformance in comparison to opaque, flexible thin-film modules such as CIGS. These results stress theimportance of developing new, highly transparent electrode and interlayer materials, along with highefficiency active layers, if the full potential of this application is going to be realised.